Replacement of Missing Anterior Teeth in a Patient with Chronic Mouth Breathing and Tongue Thrusting - Satheesh B. Haralur; Ali Saad Al-Qahtani (Hindawi Limited, 2013)
The loss of anterior teeth has serious functional, esthetic disabilities, in addition to compromising the patients' quality of life. Various etiologies can be attributed to the anterior tooth loss, including trauma, caries, and periodontal diseases. The chronic mouth breathing due to nasal adenoids is known to enhance the gingival and periodontal diseases. The dental literature proves the association of nasal breathing, tongue thrusting, and anterior open bite. Arch shape and tooth position are primarily determined by the equilibrium of the forces from tongue and perioral musculature. Increased force from tongue musculature in the tongue thrusting patient leads to flaring of anterior teeth, making them susceptible for periodontal and traumatic tooth loss. Replacement of the anterior teeth in this patient will also help in restoration of anterior guidance, which is critical for the health of temporomandibular joint, posterior teeth, and musculature.